Recent Advances in the Discovery of Biomarkers for Canine Osteosarcoma - Luu, Anita K.; Wood, Geoffrey A.; Viloria-Petit, Alicia M. (Frontiers in Veterinary Science, 2021)
Canine osteosarcoma (OSA) is an aggressive malignancy that frequently metastasizes to the lung and bone. Not only has there been essentially no improvement in therapeutic outcome over the past 3 decades, but there is also a lack of reliable biomarkers in clinical practice to discriminate which patients will most benefit from the standard treatment of amputation and adjuvant chemotherapy. The development of reliable diagnostic biomarkers could aid in the clinical diagnosis of primary OSA and metastasis; while prognostic, and predictive biomarkers could allow clinicians to stratify patients to predict response to treatment and outcome. This review summarizes biomarkers that have been explored in canine OSA to date. The focus is on molecular biomarkers identified in tumour samples as well as emerging biomarkers that have been identified in liquid biopsies, including circulating tumour cells, microRNAs, and extracellular vesicles. Lastly, we discuss obstacles to overcome to ensure biomarkers can be incorporated into a clinical setting.